PENGARUH PROFESIONALISME DAN KREATIVITAS GURU TERHADAP HASIL BELAJAR SISWA PADA SEKOLAH MENENGAH PERTAMA SWASTA NAMIRA MEDAN - Sarah Nadila; Ilham Mubaraq Ritonga; Muller Tamba (STKIP Subang, 2025)
This study aims to determine the influence of teacher professionalism and creativity on student learning outcomes, both partially and simultaneously, at Namira Private Junior High School, Medan. The sample size for this study was 156 respondents, using the Slovin formula. The analysis technique used was multiple linear regression. The results indicate that teacher professionalism has a positive and significant effect on student learning outcomes. Teacher creativity has a positive and significant effect on student learning outcomes. Teacher professionalism and creativity have a positive and significant effect simultaneously on student learning outcomes at Namira Private Junior High School, Medan